The Predictive Values of the Functional Status, Comorbidities, and the Types of Treatment on the Treatment Outcomes in Elderly Patients Following the Hip Fracture - Đozić, H; Bišćević, M; Muharemović, T; Žujo, S; Kukuljac, A; Skopljak, E (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
PURPOSE OF THE STUDY The hip fracture is the leading cause of disability and deaths in elderly. If left untreated, the hip fracture results in inability to walk, and therefore the patient is dependent on the other's people help. The aim of this study was to determine the predictive values of the functional status, present comorbidities, and the types of treatment on the long-term functional status and mortality in patients with the hip fracture. MATERIAL AND METHODS We analyzed the data about the patients with the hip fractures treated in the period between 01.07.2006. and 01.07.2016., with the mean follow-up period between 34.3±4.9 months. The data included radiographs, age, comorbidities, functional status on admission, functional status on discharge, and follow-ups. RESULTS Female sex, increasing age, and poorer functional status upon admission, conservative treatment, trochanteric fracture, the presence of neurological or lung disease, diabetes, were all significant risk factors leading to poorer functional outcomes on the latest follow-up (p < 0.05). On the other hand, the patients who were mobile upon admission had a longer survival (38.1±3.51 months) as compared with the other patients (12.3±5.1 months; χ2=25.202, p = 0.001). Besides, the results of this study revealed that the direct, statistically significant relationship exists between the untreated internal and neurological diseases, and increased mortality and poorer functional outcomes on the latest follow-up. CONCLUSIONS These results are useful for the orthopedic and trauma surgeons, who are treating these patients, the physical medicine and rehabilitation specialists, who are performing the rehabilitation of these patients, but also the health policy makers, who may promote the programmes of healthy aging (treating the diseases, maintaining fitness, etc.) Key words: hip fracture; comorbidity; mortality; functional status.
Keywords: Female; Aged; činnosti denního života; fraktury kyčle; Hip Fractures; Humans; ženské pohlaví; výsledek terapie; senioři; komorbidita; lidé; Comorbidity; Functional Status; Activities of Daily Living; Treatment Outcome; funkční status